AB0212 Peripheral blood flow cytometric activity markers in systemic lupus erythematosus. (23rd January 2014) - Schneider, S.; Rauhut, F.; Gerl, V.; Biesen, R.; Hoyer, B.F.; Cheng, Q.; Burmester, G.R.; Hiepe, F.
Abstract : Background: In Systemic Lupus Erythematosus (SLE) various compartments of the immune system are altered. Type I interferon (IFN) produced by plasmacytoid dendritic cells seems to play a central role. The expression of Sialic Acid–Binding Ig-like Lectin 1 (Siglec-1) on monocytes is a cytometrically measurable surrogate parameter for type I IFN and has been shown to correlate with disease activity in SLE. Increased B cell activation is also characteristic for active SLE. Frequencies of CD27 ++ plasmablasts in peripheral blood are known to be higher in patients with active disease. Type I IFN can promote T cell dependent and independent B cell activation. Objectives: To investigate the combined measurement of Siglec-1 expression and plasmablast frequencies as biomarkers for disease activity in human SLE. Methods: After informed consent heparinised blood samples along with clinical and paraclinical data were collected from 12 SLE patients. After red cell lysis FACS staining was performed with fluorescent antibodies against CD14, CD3, CD19, CD20, CD27, CD138 and Siglec-1 plus isotype control. Cells were collected and measured using a BD™ LSR II flow cytometer. Data were analysed using FLOWJO analysis software. For Siglec-1 expression on CD14 + monocytes a ratio was calculated dividing the median fluorescence intensity (MFI) value of Siglec-1 stained by the MFI of isotype control stained cells. Plasmablast frequencies where calculated by gating on mononuclear cells according to forward and sideward scatter, further gating on CD19 + CD3 - cells and than on CD20 - CD27 ++ or CD20 - CD138 + cells, respectively. Results: Siglec-1 expression correlated negatively with serum complement (C3) but not with SLEDAI or anti double stranded DNA (dsDNA) antibody titers using the non parametric Spearman test. Both, frequencies of CD20 - CD27 ++ and frequencies of CD20 - CD138 + cells correlated negatively with serum complement and positively with SLEDAI but not with dsDNA antibody titers. This was the case for frequencies in CD19 + B cells as well as in lymphocytes. Furthermore, Siglec-1 expression correlated positively with plasmablast frequencies, again for both, CD20 - CD27 ++ and CD20 - CD138 + cells. Conclusions: All measured parameters (Siglec-1 in monocytes, CD20 - CD27 ++ CD19+ cells and CD20 - CD138 + CD19+ cells) seem to be suitable as additional disease activity markers in SLE. The reliability of the single markers and combinations should, of course, be studied in a bigger cohort, and also under various treatment conditions. The correlation of Siglec-1 expression with plasmablast frequencies is a further hint to pathogenetic relations between type I interferon and B cell activation. References: Biesen R, Demir C, Barkhudarova F, Grün JR, Steinbrich-Zöllner M, Backhaus M, Häupl T, Rudwaleit M, Riemekasten G, Radbruch A, Hiepe F, Burmester GR, Grützkau A. Sialic acid-binding Ig-like lectin 1 expression in inflammatory and resident monocytes is a potential biomarker for monitoring disease activity and success of therapy in systemic lupus erythematosus. Arthritis Rheum. 2008 Apr;58(4):1136-45. Jacobi AM, Odendahl M, Reiter K, Bruns A, Burmester GR, Radbruch A, Valet G, Lipsky PE, Dörner T. Correlation between circulating CD27high plasma cells and disease activity in patients with systemic lupus erythematosus. Arthritis Rheum. 2003 May;48(5):1332-42. Disclosure of Interest: None Declared